2018
DOI: 10.1542/hpeds.2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parental Preferences for Participants in Medical Decision-making for Their Hospitalized Children

Abstract: Parents of hospitalized children want to participate in medical decision-making. Desire for the involvement of other family members is complex; therefore, discussions regarding parental preferences are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Some parents who have experienced shared medical decision making reported feeling that healthcare providers present information in a manner that encourages parents to agree with the healthcare provider recommendations. 46,47 The experience of the 22-week GA mother, referenced in the results, highlights how the P3 app can empower parents to effectively advocate their treatment preference to the medical team. We envision that the smartphone based education will supplement and not replace the information parents receive during preterm birth hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some parents who have experienced shared medical decision making reported feeling that healthcare providers present information in a manner that encourages parents to agree with the healthcare provider recommendations. 46,47 The experience of the 22-week GA mother, referenced in the results, highlights how the P3 app can empower parents to effectively advocate their treatment preference to the medical team. We envision that the smartphone based education will supplement and not replace the information parents receive during preterm birth hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Family deliberation is especially important for preterm birth decision making as research reveals that for high risk decisions the preference is to share the burden of decision making with the other parent. 46 Most P3 app users reported that because of the app they discussed pregnancy and prematurity issues with their partner and shared information with other family members.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that the mean score on satisfaction with parental participation was significant. Additionally, as in other studies, involving parents in childcare was very important for the participant parents and increased their satisfaction with their children's healthcare (Dadlez et al, 2018).…”
Section: Discussionmentioning
confidence: 59%
“…From parents' point of view, effective treatment and care for their children, and a desire to maintain these factors, are universal (Disch & Adwan, 2014). The presence of parents and their participation in care is an aspect of caregiving that should not be ignored because it reduces emotional stress in the child, increases their feeling of trust, enables the child to cope with anxiety during hospitalization and protects the parent–child relationship while meeting the needs of both parties (Dadlez, Bisono, Williams, Rosenthal, & Hametz, 2018; Daneman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the changes families would like to see are reported by caregivers of individuals with other rare conditions as well. This desire of family caregivers to improve care by including aspects of FCC has been noted in numerous studies (Dadlez et al, 2018;Michael et al, 2014;Uhl et al,2013). The desire to increase collaboration between family caregivers with their indepth knowledge and lived experience of providing care to a loved one with a rare condition and healthcare providers has been noted by both caregivers (Currie & Szabo, 2019) and members in the medical community (Baumbusch et al, 2018), with an understanding that listening to patient feedback would help develop a greater trusting relationship between the two (Gómez-Zúñiga et al, 2019).…”
Section: Discussionmentioning
confidence: 98%